EFFECTS OF MICROALGAE SPIRULINA Arthrospira platensis SUPPLEMENTATION TO THE PLANT-BASED DIET FOR PACIFIC WHITE SHRIMP Litopenaeus vannamei - Romi Novriadi; Fira Irawan; Shadiqa Malahayati; Nurul Khotimah; Ofan Bosman; Budi Tanaka; Jovano Erris Nugroho (Agency for Marine and Fisheries Extension and Human Resources, 2022)
A sixty-days feeding trial was conducted to evaluate the inclusion effect of spirulina Arthrospira platensis meal (SM) in the diet on growth and health condition of juvenile Pacific white shrimp Litopenaeus vannamei. Four isonitrogenous and iso-lipidic experimental diets were formulated to contain 0%, 0,2%, 0,4% and 0,8% SM. After 60 days, shrimp were sampled and total haemocyte counts was measured. The growth performances of shrimp were significantly affected by the dietary inclusion of SM, whereas the inclusion of SM provides a better biomass, final body weight (FBW), weight gain (WG) and feed conversion ratio (FCR) compared to the control group. Additionally, the inclusion of SM significantly enhances the total haemocytes count (THC) and lysozyme activity in shrimp compared to control group. Therefore, SM can be considered as the functional ingredients in shrimp diet to improve the growth and health condition of shrimp.